Comparison of effects on the oxidant/antioxidant system of sevoflurane, desflurane and propofol infusion during general anesthesia - Erbas,Mesut (2015)
BACKGROUND AND OBJECTIVES: Desflurane and sevoflurane are frequently used for maintenance of anesthesia and studies have shown that these anesthetics cause a variety of changes to the oxidative stress and antioxidative defense mechanisms. This study aims to compare the effects of sevoflurane, desflurane and propofol infusion anesthesia on the oxidant and antioxidant systems of patients undergoing laparoscopic cholecystectomy. METHODS: 45 patients between 18 and 50 years with planned laparoscopic cholecystectomy under general anesthetic were included in the study. Patients were divided into three groups on the way to surgery: propofol (group P n: 15), sevoflurane (group S n: 15) and desflurane (group D n: 15). All groups were given hypnotic 2 mg/kg propofol IV, 1 mcg/kg fentanyl IV and 0.1 mg/kg vecuronium IV for induction. For maintenance of anesthesia group S were ventilated with 2% sevoflurane, group D cases were given 6% desflurane and group P were given propofol infusions of 12 mg/kg/h for the first 10 min, 9 mg/kg/h for the second 10 min and 6 mg/kg/h after that. Before induction and after the operation venous blood samples were taken to evaluate the levels of glutation peroxidase, total oxidants and antioxidants. RESULTS AND CONCLUSIONS: The 45 patients included in the study were 22 male and 23 female patients. The demographic characteristics of the groups were similar. In the postoperative period we observed that while sevoflurane and propofol increased antioxidants by a statistically significant level, desflurane increased the total oxidants level by a significant amount compared to levels before the operation.